Evaluating the Tire/Pavement Noise and Surface Texture of Low-Noise Micro-Surface Using 3D Digital Image Technology - Chen, Wang; Zheng, Mulian; Wang, Haiyang (Frontiers in Materials, 2021)
As a common preventive maintenance technique for asphalt pavement, micro-surface (MS) has the advantages of waterproofing, crack sealing. However, the conventional MS generates large noise, the evaluation indexes of tire-road noise are relatively less studied, and the traditional surface texture index cannot reveal the range and distribution of pavement surface texture, thus hindering the research of low-noise MS. In order to study the mechanism of tire-road noise generated by MS, and propose the tire-road noise and surface texture indicators for MS. In this study, the mechanism of five low-noise MS was systematically analyzed and compared through surface texture and noise tests. Then, a three-dimensional digital texture model (3D-DTM) of MS surface texture was constructed by using a series of digital image processing techniques, including grayscale identification, binary conversion, and noise reduction. The results show that optimizing the gradation, adding sound-absorbing materials, and improving the workability of construction can improve the noise reduction performance of MS, it is worth mentioning that the MS prepared with sound-absorbing materials and low-noise gradation has the greatest noise reduction effect, with a maximum reduction of 6.3dB(A). In addition, it was also found that the 3D-DTM can well reflect the surface texture characteristics of MS. The probability of convex peak distribution (PCD) and the proportion of convex peak area (PCA) with peak heights greater than 0.25 mm (Kh≥0.25), which extracted from the 3D-DTM can well reflect the surface texture, tire-road noise, respectively. The results show that the 3D-DTM is a promising tool to optimize the design of low-noise MS.